2013
DOI: 10.1111/jphp.12094
|View full text |Cite
|
Sign up to set email alerts
|

Isoniazid-gelatin conjugate microparticles containing rifampicin for the treatment of tuberculosis

Abstract: Overall, microparticles based on gelatin covalently bound to ISN and containing RFP showed a promising behaviour for pulmonary drug delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(11 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Rawat et al reported that heparin-loaded PLGA microspheres produced by double emulsion techniques were within the inhalable size range, but both the entrapment efficiency (up to 55%) and half-life (up to 6-fold) were only increased by the addition of chemical additives (Rawat et al, 2008). Manca and co-workers also developed carriers for pulmonary administration of rifampicin based on gelatin (Manca et al, 2013) and polymer-coated liposomes (Manca et al, 2014), which displayed good aerodynamic properties and an efficient drug internalization by A540 cells.…”
Section: Introductionmentioning
confidence: 99%
“…Rawat et al reported that heparin-loaded PLGA microspheres produced by double emulsion techniques were within the inhalable size range, but both the entrapment efficiency (up to 55%) and half-life (up to 6-fold) were only increased by the addition of chemical additives (Rawat et al, 2008). Manca and co-workers also developed carriers for pulmonary administration of rifampicin based on gelatin (Manca et al, 2013) and polymer-coated liposomes (Manca et al, 2014), which displayed good aerodynamic properties and an efficient drug internalization by A540 cells.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, antibiotics for inhalation can be packaged in synthetic nanoparticles or natural polymeric microparticles, such as gelatin. 120 In the future, nanotechnology may be used to target antibiotics to particular regions of the lung to allow drug delivery to specific sites of disease. One way of doing this is by delivering magnetic nanoparticles with the antibiotic solution.…”
Section: Inhaled Antibiotic Delivery Systems-innovationsmentioning
confidence: 99%
“…While these have shown satisfactory in vitro performance and stability, the nebulized formulation still needs refinement of endotoxin levels to meet regulatory standards. Finally, Manca et al (198) developed a nebulized suspension of isoniazid-gelatin conjugate microparticles containing rifampicin, which reduced toxicity to A549 alveolar epithelial cells compared to a rifampicin solution. This demonstrated that the use of nebulized antibiotics for diseases not conventionally treated by nebulization.…”
Section: New Therapeuticsmentioning
confidence: 99%